2021
DOI: 10.30773/pi.2020.0155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive-Behavioral Therapy Based Music Therapy in Korean Adolescents with Smartphone and Internet Addiction

Abstract: Objective The purpose of this study was to evaluate the effects of adding music therapy (MT) to cognitive-behavioral therapy (CBT) on symptoms of smartphone/internet addiction and psychiatric comorbidities.Methods Overall, 155 patients diagnosed with addiction were assigned to either the CBT-MT group or CBT group. Both groups received CBT for 8 weeks, while the CBT-MT group received additional MT. The intervention was completed by 67 and 71 participants in the CBT-MT and CBT groups, respectively.Results The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In contrast, the study by Bong et al [45] combined the intervention based on cognitive behavioral theory with music therapy. These authors observed significant decreases in the scores of the addictions to smartphones and the Internet after the cognitive behavioral program and the program combining cognitive behavioral therapy and music therapy.…”
Section: Programs Based On Cognitive Behavioral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the study by Bong et al [45] combined the intervention based on cognitive behavioral theory with music therapy. These authors observed significant decreases in the scores of the addictions to smartphones and the Internet after the cognitive behavioral program and the program combining cognitive behavioral therapy and music therapy.…”
Section: Programs Based On Cognitive Behavioral Therapymentioning
confidence: 99%
“…Other works have gone one step further by combining cognitive behavioral therapy with music therapy. This is the case of the work of Bong et al [45], who applied the synergistic interventions of both therapies as a treatment for Internet addiction, observing not only less problematic use of the Internet, but also fewer anxiety symptoms and less impulsivity than when only cognitive behavioral therapy was applied. These authors argue that music therapy not only relaxes participants emotionally and allows them to experience intimacy with the therapist and with group members, but also encourages the performance of cognitive behavioral therapy tasks, in addition to inducing interest in the group therapy and adaptations to it.…”
Section: Programs Based On Cognitive Behavioral Therapymentioning
confidence: 99%
“…On the other hand, MPA may also affect the level of alexithymia. According to cognitive-behavioral theory, individuals' cognitions and emotions could not only affect their behaviors but also be influenced by their own behaviors ( 89 ). Students with a high degree of MPA tend to neglect offline social communication, which reduces the time and opportunities for offline communication with friends and family and has a negative impact on the establishment of a social emotional support system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the non-threatening nature that music therapy can offer in therapeutic processes with adolescents makes it easier for these to occur without patient resistance (Brooks, 1989). On this some research suggests that the use of music therapy in union with cognitive-behavioral therapy techniques is an effective combination in therapeutic processes with adolescents (Bong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%